Termorregulação de ovinos morada nova - Fonsêca, Vinícius de França Carvalho (2016)
The objective of this study was to evaluate the thermorregulation of Morada Nova sheep using an indirect calorimetry system. In order to develop a methodology for habituation and conditioning of animals for testing with the indirect calorimetry system, sixteen Morada Nova sheep with 32.6 ± 1.8 kg body weight and 2.8 ± 0.9 years old were selected from a herd of 60. The duration of the training period was 83 days, which was divided into three steps. From the second step, physiological and behavioral traits were used as indicators of aversive response to the procedures used. When the time spent by the animals in the contention trunk with facial mask increased from 10 to 50 minutes, the respiratory rate did not change. The probability of the sheep to show resistance at the time of the rise in the trunk decreased with the increase in time spent in the contention trunk, becoming practically nil at the end of the 3rd step. At the end of this phase, twelve animals with 32.76 ± 3.72 kg body weight were distributed in two Latin squares 12 x 12 (24 hours and 24 days of records). Animals were evaluated from 07:00 to 18:00 (QL1) and from 19:00 to 06:00 hours (QL2), kept in the shade and sheltered overnight. Ventilation rate (VE), breathing rate (F), temperature (TE), the vapor pressure (e[TE]), percentage of oxygen (O2) and carbon dioxide (CO2) from the exhaled air were quantified by an indirect calorimetry system. The animal's heat balance was quantified according to the principles of energy conservation law. In the range of 00:00 to 06:00 h, sensible heat flow became twice that the heat produced by metabolism. In a temperature range higher than 30 and minor than 32 ° C, latent heat (q"er) became important in the thermal balance. A simple non-linear model to estimate the tidal volume (VRC) as a function of respiratory frequency (F) was developed. An equation to calculate the temperature of the expired air (TE) was built and the air temperature was the best estimator, together with the relative humidity and atmospheric vapor pressure. Functions presented in this study allow to estimate the sensible and latent heat flux form the respiratory tract of Morada Nova sheep under field, using physiological and environmental simple parameters as respiratory rate, air temperature and relative humidity. For Morada Nova sheep protected from solar radiation, wind and rain, a minimum thermoregulatory effort is obseved under temperature range of 22 and 30 °C